Managing the hidden burden: psychological safety as a strategic buffer between nurse mental workload and somatization - Fatma Demirkaya; Demet Yurtsever; Merve Murat Mehmed Ali; Merve Saritaş; Elvan Emine Ata (Journal of Health Organization and Management, 2026)
Purpose This study examines the relationship between mental workload and somatization symptoms in nurses, focusing on the role of psychological safety as a mediating factor and investigates the role of psychological safety as a strategic resource in mitigating the negative physiological consequences of high cognitive demands in hospital management. Design/methodology/approach The study employed a cross-sectional, correlational research design. Data were collected from 422 nurses working at a public training and research hospital in Istanbul, Türkiye. The Mental Workload Scale, Psychological Safety Scale, and Somatization Scale were used in the study. Theoretical relationships were tested using the Job Demands-Resources (JD-R) framework and analyzed using Hayes' PROCESS macro (Model 4) with 5.000 bootstrap resamples. Findings The results indicate that mental workload is a significant organizational stress factor positively associated with somatization. Psychological safety was found to statistically account for part of this relationship. Consistent with the JD-R framework, psychological safety appears to function as a resource associated with a weaker statistical association between mental workload and somatic tension. Originality/value This study contributes to the JD-R literature in two ways: Firstly, it focuses on somatization, a health outcome that has received limited attention in the field of nursing. Secondly, it empirically examines the mediating role of psychological safety in the process by which high mental workload is transformed into somatic symptoms.